2017
DOI: 10.29252/nirp.ijpcp.23.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cognitive, Metacognitive, and Meta-Emotional Components in Prediction of Emotional Distress in Students

Abstract: ObjectivesThe study aims to investigate the role of cognitive , metacognitive and meta-emotional components in predicting emotional distress in college students. Methods This is a descriptive correlation study, and the study sample consisted of 400 college students who were selected by multistage cluster sampling. Data were obtained using Emotion Regulation Scale (ERS), Leahy Emotional Schemas Scale (LESS), Schema Questionnaire-Short Form (SQ-SF), Meta Cognition Questionnaire (MCQ-30), Mindful Awareness Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Based on the findings, it can be said that acceptance and commitment-based couples therapy has been effective in emotional regulation in married women. These results are consistent with the prior research (Ahadian fard et al, 2017;Ahmadi & Raeisi, 2018;Amir et al, 2019;Azandariani et al, 2022;Baseri & Bozorgi, 2017;Caletti et al, 2022;Darvish Baseri & Dashtbozorgi, 2017;Flujas-Contreras & Gómez, 2018;Ghadampour et al, 2019;Ghahari et al, 2021;Ghorbani Amir et al, 2019;Heshmati et al, 2018;Iri et al, 2019). In explaining this hypothesis, it can be said that couples therapy based on commitment and acceptance, by properly releasing emotions, stabilizing attachment styles, and reducing emotional and anxiety problems, leads to an increase in their physical health.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the findings, it can be said that acceptance and commitment-based couples therapy has been effective in emotional regulation in married women. These results are consistent with the prior research (Ahadian fard et al, 2017;Ahmadi & Raeisi, 2018;Amir et al, 2019;Azandariani et al, 2022;Baseri & Bozorgi, 2017;Caletti et al, 2022;Darvish Baseri & Dashtbozorgi, 2017;Flujas-Contreras & Gómez, 2018;Ghadampour et al, 2019;Ghahari et al, 2021;Ghorbani Amir et al, 2019;Heshmati et al, 2018;Iri et al, 2019). In explaining this hypothesis, it can be said that couples therapy based on commitment and acceptance, by properly releasing emotions, stabilizing attachment styles, and reducing emotional and anxiety problems, leads to an increase in their physical health.…”
Section: Discussionsupporting
confidence: 91%
“…Elders who score higher in experiential avoidance face higher emotional distress and negative cognitions. In relation to the role of experiential avoidance in predicting distress tolerance in the elderly, it can be stated that from the perspective of ACT, experiential avoidance leads to efforts to suppress emotions, thoughts, and other internal experiences, resulting in psychological inflexibility that leads to emotional disorders (Ahadian fard et al, 2017;Angiola & Bowen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the research conducted, it appears that grief most significantly affects the quality of object relations and is considered a threatening factor (Holaday & Glidewell, 2000;Poshtareh et al, 2023). Disturbances in object relations undermine the foundations of personal security and lead to increased vulnerability to grief (Ahadian fard et al, 2017;Orang et al, 2018). Numerous studies have confirmed the hypothesis that mental health is significantly related to defense mechanisms (Besharat, 2008;Blanco et al, 2023;Brockman et al, 2016;Brody & Carson, 2012;Conversano et al, 2023;Cramer, 1987Cramer, , 2002Giuseppe & Perry, 2021;Jamilian et al, 2014;Jun et al, 2015;Lee et al, 2020;Lotfi-Hajilo et al, 2017;Mesgarian et al, 2017;Poshtareh et al, 2023;Rubino et al, 2007).…”
Section: Introductionmentioning
confidence: 98%